Podcasting to sensitize gender equity in English language student teachers - Guaranda Paredes, Fernando Daniel; Palma Cedeño, Nixon Nicolás; Villafuerte-Holguin, Jhonny (Technium Education and Humanities, 2025)
Gender equity remains a challenge that must be addressed across all areas of the education system. This study aims to explore the potential of podcasts to foster reflection on gender inequality in education. The research adheres to the postmodern paradigm and a quantitative approach. Participants are 94 student teachers enrolled in the English as a Foreign Language teacher training program at a public university in Ecuador. Data was collected using a Likert-type questionnaire, a survey, and an information sheet. The results include pre- and post-test findings on knowledge, attitudes, and motivations for podcast production. The study concludes that podcasts offer opportunities for reflection, research, transformation, and dissemination of information on socioeconomic issues such as gender equity in a controlled environment. It also concludes that the planning, production, and distribution of podcasts represent a way to overcome challenges related to soft skills, particularly when using a foreign language. This is an innovative practice that makes a significant contribution to the training process of professionals who respond to the pedagogical and communicative demands of the 21st century.